Implikasi Putusan MK No. 65/Puu-Xxi/2023 Terhadap Prinsip Keadilan Pemilu di Indonesia - A, Amelia; Faisal, Adhiya; Rachma, Ayzza; Okhtiara, Farizka (Media Hukum Indonesia (MHI), 2025)
The reason for this investigation is the decision of the Constitutional Court No. 65/PUU-XXI/2023, which allows general election campaigns in educational institutions as long as they do not use electoral attributes. However, in Law No. 7 of 2023, Article 280(1)(h) emphasizes that general election campaigns in state institutions or educational institutions are not justified. The background of the research relates to the legal considerations contained in Decision No. 65/PUU-XXI/2023 of the Constitutional Court to ensure the principle of electoral justice in Indonesia, as well as the impact of Decision No. 65/PUU-XXI/2023 of the Constitutional Court on the organization of elections in Indonesia based on the principle of electoral justice. The aim of this study is to determine the legal analysis of Constitutional Court Decision No. 65/PUU-XXI/2023 and to examine the impact of Constitutional Court Decision No. 65/PUU-XXI/2023 on the organization of elections in Indonesia based on the principles of electoral justice. This research uses normative legal methods and the method of data collection is in the form of library research. The sources of this research include books, laws and regulations related to this research. The outcome of this research is that the results indicate that the decision has the possibility of eliminating the difference between the world of education and direct political activity. This may undermine the neutrality of ASN and create inequality in access to the polls. There are also concerns that the presence of campaigning in educational institutions will compromise the independence of educational institutions and disrupt the teaching and learning process. Therefore, strict derivative rules are needed to regulate the implementation of this decision and uphold the principle of fairness in elections.